Antibiotics profile map of clinical A. baumannii strains isolated from health institutions in Turkey: a database search study and analysis of publications from 2011 to 2022 - Abed, Ahmed Badri (2023)
Acinetobacter baumannii is recognized as a major threat that causes healthcare-associated infections and causes a huge challenge to the health system worldwide. This research study was designed to detect the types and profiles of antibiotics tested against A. baumannii clinical strains in Turkey to evaluate their effectiveness and reevaluate their usage.